Cordierite ceramic carrier and preparation method thereof

The thin-walled cordierite ceramic carrier is prepared through specific raw material formula and firing process, which solves the problem of large thermal expansion coefficient of the catalyst carrier, achieves low thermal expansion coefficient and high heat resistance, and quickly ignites through the heating device, significantly reducing exhaust emissions .

CN119118640APending Publication Date: 2024-12-13DONGFENG MOTOR GRP

Patent Information

Application Number
CN202411204611.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing automotive catalyst carrier has a large thermal expansion coefficient, which is difficult to meet the demand for reducing exhaust emissions.

Method used

Prepare thin-walled cordierite ceramic carriers using specific raw material formulas and firing processes, including raw kaolin, calcined kaolin, talc, alumina and silica. Prepare through dry mixing, kneading, extrusion molding, drying and calcining steps such as A ceramic carrier with a low coefficient of thermal expansion is provided, and a heating device can be optionally equipped to improve the ignition efficiency of the catalyst.

Benefits of technology

The prepared ceramic carrier has a low linear expansion coefficient, a heat shock resistance temperature greater than 800℃, a softening temperature greater than 1480℃, and a catalyst ignition temperature is quickly reached through a heating device, which significantly reduces the exhaust emissions during the vehicle startup stage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118640A_ABST
    Figure CN119118640A_ABST
Patent Text Reader

Abstract

The invention relates to a cordierite ceramic carrier and a preparation method thereof, and belongs to the technical field of automobile exhaust treatment. The method comprises the steps that raw materials are subjected to dry mixing to obtain a dry material, and the raw materials comprise, by mass, 8-16 parts of raw kaolin, 0-25 parts of calcined kaolin, 39-41 parts of talc, 8-22 parts of aluminum oxide and 4-15 parts of silicon dioxide; mixing an auxiliary agent with a solvent to obtain a wet material; kneading the dry material and the wet material to obtain a mixture; carrying out extrusion forming on the mixture to obtain a blank; the blank is dried and then roasted, and the cordierite ceramic carrier is obtained; by selecting specific raw materials, the prepared cordierite ceramic carrier has a relatively low thermal expansion coefficient, the linear expansion coefficient of the cordierite ceramic carrier is 0.17 * 10 <-6 >-0.28 * 10 <-6 > DEG C <-1 >, the thermal shock resistance temperature of the cordierite ceramic carrier is greater than 800 DEG C, the softening temperature of the cordierite ceramic carrier is greater than 1480 DEG C, the cordierite phase is greater than or equal to 93%, and the cordierite ceramic carrier has relatively good comprehensive performance. The raw materials of the method are easy to obtain, and the method is suitable for industrial batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of automobile exhaust treatment, and in particular to a cordierite ceramic carrier and a preparation method thereof. Background Art

[0002] While cars have brought great convenience to people's lives, they have also brought some adverse factors that affect the ecological environment. About 70% of fuel vehicles still use fossil fuels. The combustion of such fuels not only produces greenhouse gas carbon dioxide, but also many byproducts that pollute the environment, such as carbon monoxide, hydrocarbons, nitrogen oxides and particulate matter. In some cities, automobile exhaust emissions can even account for more than 50% of air pollution. All major automakers are committed to reducing automobile exhaust emissions, but the thermal expansion coefficient of existing automobile catalyst carriers still has a lot of room for improvement. Summary of the invention

[0003] The present application provides a cordierite ceramic carrier and a preparation method thereof, which can improve the thermal expansion coefficient of the catalyst carrier.

[0004] In a first aspect, the present application provides a method for preparing a cordierite ceramic carrier, the method comprising:

[0005] dry-mixing the raw materials to obtain a dry material, wherein the raw materials include, by mass fraction, 8 to 16 parts of raw kaolin, 0 to 25 parts of calcined kaolin, 39 to 41 parts of talc, 8 to 22 parts of alumina, and 4 to 15 parts of silicon dioxide;

[0006] The auxiliary agent is mixed with the solvent to obtain a wet material;

[0007] kneading the dry material and the wet material to obtain a mixed material;

[0008] Extruding the mixed material to obtain a blank;

[0009] The green body is dried and then calcined to obtain a cordierite ceramic carrier.

[0010] As an optional embodiment, in the raw kaolin, the mass content of Al2O3 is ≥37.50%, and the mass content of SiO2 is ≥48.75%; and / or

[0011] The mass loss on ignition of the raw kaolin is ≤13.0%; and / or

[0012] The raw kaolin is in the form of flakes; and / or

[0013] The D 50 7 μm to 9 μm; and / or

[0014] The D 100 ≤63μm; and / or

[0015] The diameter-to-thickness ratio of the raw kaolin is ≥30; and / or

[0016] In the raw kaolin, the mass content of K2O and Na2O is less than 0.5%, the mass content of Fe2O3 is less than or equal to 0.3%, and the mass content of TiO2 is less than or equal to 2.0%.

[0017] As an optional embodiment, in the calcined kaolin, the mass content of Al2O3 is ≥43%, and the mass content of SiO2 is ≥52%; and / or

[0018] The calcined kaolin is in the form of flakes; and / or

[0019] The D 50 2 μm to 7 μm; and / or

[0020] The D 100 ≤63μm; and / or

[0021] The diameter-to-thickness ratio of the calcined kaolin is ≥30; and / or

[0022] In the calcined kaolin, the mass content of K2O and Na2O is less than 0.5%, the mass content of Fe2O3 is less than or equal to 0.3%, and the mass content of TiO2 is less than or equal to 2.0%.

[0023] As an optional embodiment, in the talc, the mass content of Al2O3 is ≥62.54%, and the mass content of MgO is ≥29.79%; and / or

[0024] The mass loss on ignition of the talc is ≤13.0%; and / or

[0025] The talc is in the form of flakes; and / or

[0026] The D of talc 50 13 μm to 14 μm; and / or

[0027] The D of talc 100 ≤63μm; and / or

[0028] The diameter-to-thickness ratio of the talc is ≥30; and / or

[0029] In the talc, the mass content of CaO is ≤0.1%, the mass content of K2O and Na2O is <0.5%, the mass content of Fe2O3 is ≤0.9%, the mass content of TiO2 is ≤2.0%, and the mass content of TiO2 is ≤0.1%.

[0030] As an optional embodiment, the mass content of Al2O3 in the aluminum oxide is ≥99%; and / or

[0031] The D of the aluminum oxide 50 5 μm to 7 μm; and / or

[0032] The diameter-to-thickness ratio of the aluminum oxide is ≥1; and / or

[0033] In the aluminum oxide, the mass content of Fe2O3 is ≤0.003%, and the mass content of TiO2 is ≤0.03%.

[0034] As an optional embodiment, the mass content of SiO2 in the silicon dioxide is ≥99%; and / or

[0035] The silicon dioxide satisfies: D 10 7.2~9.2μm, D 50 10.8~12.5μm, D 90 16.9 to 22 μm; and / or

[0036] The particle size distribution parameter K of the silicon dioxide is 90 -D 10 ) / D 50 ) is 0.6~1.

[0037] As an optional embodiment, the raw material further comprises ultrafine nanometer active oxides, and the components of the ultrafine nanometer active oxides include Al2O3 and SiO2; and / or

[0038] In the ultrafine nanometer active oxide, the mass ratio of Al2O3 to SiO2 is (0.5-1.5): (0.5-1.5); and / or

[0039] The particle size of the ultrafine nano-scale active oxide is 20nm to 500nm; and / or

[0040] The mass fraction of the ultrafine nanometer active oxide in the raw material is 8 to 12 parts.

[0041] As an optional embodiment, the raw material further comprises a functional additive, wherein the functional additive comprises nano-aloe vera powder and / or blue algae powder; and / or

[0042] The mass fraction of the functional additive in the raw material is 0.1 to 0.5 parts; and / or

[0043] The particle size of the functional additive is 20nm to 400nm.

[0044] As an optional embodiment, the drying temperature rise rate is 6°C / min to 10°C / min, the drying temperature is 90°C to 110°C, and the drying time is 1h to 2h; and / or

[0045] The calcination comprises a first calcination, a second calcination, a third calcination and a fourth calcination; and / or

[0046] The heating rate of the first calcination is 35°C / min to 45°C / min, the temperature of the first calcination is 150°C to 250°C, the time of the first calcination is 0.5h to 1.5h, and the atmosphere of the first calcination is air atmosphere; and / or

[0047] The heating rate of the second calcination is 15°C / min to 25°C / min, the temperature of the second calcination is 450°C to 550°C, the time of the second calcination is 0.5h to 1.5h, and the atmosphere of the second calcination is a nitrogen atmosphere; and / or

[0048] The heating rate of the third calcination is 45°C / min to 55°C / min, the temperature of the third calcination is 750°C to 850°C, the time of the third calcination is 0.5h to 1.5h, the atmosphere of the third calcination is a protective gas atmosphere, and the protective period includes at least one of helium, neon and argon; and / or

[0049] The heating rate of the fourth calcination is 55°C / min to 65°C / min, the temperature of the fourth calcination is 1200°C to 1400°C, the time of the fourth calcination is 11h to 13h, the atmosphere of the fourth calcination is a protective gas atmosphere, and the protective period includes at least one of helium, neon and argon.

[0050] In a second aspect, the present application provides a cordierite ceramic carrier, wherein the cordierite ceramic carrier is a cordierite ceramic carrier prepared by the method described in any embodiment of the first aspect.

[0051] As an optional embodiment, the cordierite ceramic carrier includes a carrier body and a heating device, the carrier body includes a carrier prepared by the method provided in the first aspect, and the heating device is installed on the carrier body; and / or

[0052] The heating device comprises an electric heating device or an electromagnetic heating device; and / or

[0053] The carrier body comprises a first section and a second section, the first section is close to the air inlet end of the carrier body, and the heating device is installed on the first section.

[0054] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0055] The method provided in the embodiment of the present application, by selecting specific raw materials, makes the obtained thin-walled cordierite ceramic carrier (750 / 2 and 900 / 2) have a lower thermal expansion coefficient, and its linear expansion coefficient is 0.17*10-6 ~0.28*10 -6 ℃ -1 The heat shock resistance temperature is greater than 800°C, the softening temperature is greater than 1480°C, and the cordierite phase is ≥93%, which has good comprehensive performance. In addition, the raw materials of this method are easy to obtain and suitable for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0057] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0058] Figure 1 A flowchart of the method provided in the embodiment of the present application. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0060] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0061] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, the present application embodiment provides a method for preparing a cordierite ceramic carrier, the method comprising:

[0062] S1. dry-mixing the raw materials to obtain a dry material, wherein the raw materials include 8 to 16 parts of raw kaolin, 0 to 25 parts of calcined kaolin, 39 to 41 parts of talc, 8 to 22 parts of alumina and 4 to 15 parts of silicon dioxide by mass fraction

[0063] In some embodiments, the raw kaolin satisfies the following conditions: the mass content of Al2O3 in the raw kaolin is ≥37.50%, the mass content of SiO2 is ≥48.75%; the mass loss of the raw kaolin is ≤13.0%; the raw kaolin is in the form of flakes; the D 50 7μm~9μm; D 100 ≤63μm; the diameter-to-thickness ratio of the raw kaolin is ≥30; in the raw kaolin, the mass content of K2O and Na2O is <0.5%, the mass content of Fe2O3 is ≤0.3%, and the mass content of TiO2 is ≤2.0%.

[0064] In some embodiments, the calcined kaolin satisfies the following conditions: the mass content of Al2O3 in the calcined kaolin is ≥43%, the mass content of SiO2 is ≥52%; the calcined kaolin is in the form of flakes; the D 50 2μm~7μm; D 100 ≤63μm; the diameter-to-thickness ratio of the calcined kaolin is ≥30; in the calcined kaolin, the mass content of K2O and Na2O is <0.5%, the mass content of Fe2O3 is ≤0.3%, and the mass content of TiO2 is ≤2.0%.

[0065] In some embodiments, the talc satisfies the following conditions: in the talc, the mass content of Al2O3 is ≥62.54%, the mass content of MgO is ≥29.79%; the mass loss of the talc is ≤13.0%; the talc is in the form of flakes; the D 50 is 13 μm to 14 μm; the D 100 ≤63μm; the diameter-to-thickness ratio of the talc is ≥30; in the talc, the mass content of CaO is ≤0.1%, the mass content of K2O and Na2O is <0.5%, the mass content of Fe2O3 is ≤0.9%, the mass content of TiO2 is ≤2.0%, and the mass content of TiO2 is ≤0.1%.

[0066] In some embodiments, the mass content of Al2O3 in the aluminum oxide is ≥ 99%; 50 The diameter-to-thickness ratio of the aluminum oxide is ≥1; and the mass content of Fe2O3 in the aluminum oxide is ≤0.003%, and the mass content of TiO2 is ≤0.03%.

[0067] In some embodiments, the mass content of SiO2 in the silicon dioxide is ≥ 99%; the silicon dioxide satisfies: D 10 7.2~9.2μm, D 50 10.8~12.5μm, D 9016.9 to 22 μm; the particle size distribution parameter K of the silicon dioxide is ((D 90 -D 10 ) / D 50 ) is 0.6~1.

[0068] In some embodiments, the raw material further includes ultrafine nanometer active oxides, and the ultrafine nanometer active oxides meet the following conditions: the composition of the ultrafine nanometer active oxides includes Al2O3 and SiO2; in the ultrafine nanometer active oxides, the mass ratio of Al2O3 and SiO2 is (0.5-1.5): (0.5-1.5); the particle size of the ultrafine nanometer active oxide is 20nm-500nm; the mass fraction of the ultrafine nanometer active oxide in the raw material is 8-12 parts. The introduction of ultrafine nanometer active oxides further reduces the particle size of the powder in the entire raw material to the nanometer level, which can reduce the activation energy of the reaction, increase the reaction rate, promote the rapid growth of cordierite crystals, and improve the completion of the reaction. At the same time, it reduces the content of the impurity phase, increases the content and regularity of the cordierite crystals, and thus improves the strength of the entire carrier, giving the entire carrier better bending strength and a lower elastic modulus.

[0069] In some embodiments, the raw material further includes a functional additive, and the functional additive meets the following conditions: the functional additive includes nano-grade aloe vera powder and / or blue algae powder; the mass fraction of the functional additive in the raw material is 0.1 to 0.5 parts; the particle size of the functional additive is 20nm to 400nm. The addition of nano-grade aloe vera powder and / or blue algae powder can increase the sintering success rate of the carrier by more than 95%.

[0070] S2. mixing the additive with the solvent to obtain a wet material;

[0071] In some embodiments, the auxiliary agent includes a binder, corn starch hydrolysate, and a lubricant. The solvent may be selected from water. The mixing ratio of the binder and corn starch hydrolysate (mass ratio: 1:6, DE value ≤ 18), the lubricant and the solvent may be 3:1:12.

[0072] S3. The dry material and the wet material are kneaded to obtain a mixture;

[0073] In some embodiments, the mixing ratio of the dry material to the wet material is 60-70:30-40. In this embodiment, the mixing ratio of the dry material to the wet material can be 68:32.

[0074] Specifically, in this embodiment, the dry material and the wet material are mixed and stirred (800-1200 r / min) in a ratio of 68:32, stirred for 30 minutes, and then put into a kneading machine for kneading and slurrying for 10 minutes to obtain a mixed material.

[0075] S4. The mixture is extruded to obtain a billet;

[0076] Specifically, in this embodiment, a thin-wall honeycomb structure is obtained by extrusion molding at a speed of 10-15 cm / min and a pressure of 10-12 MPa to obtain a billet.

[0077] S5. Dry the green body, and then calcine it to obtain a cordierite ceramic carrier.

[0078] In some embodiments, the drying temperature rise rate is 6°C / min to 10°C / min, the drying temperature is 90°C to 110°C, and the drying time is 1h to 2h.

[0079] In some embodiments, the calcination includes a first calcination, a second calcination, a third calcination, and a fourth calcination. Further, the heating rate of the first calcination is 35°C / min to 45°C / min, the temperature of the first calcination is 150°C to 250°C, the time of the first calcination is 0.5h to 1.5h, and the atmosphere of the first calcination is an air atmosphere; the heating rate of the second calcination is 15°C / min to 25°C / min, the temperature of the second calcination is 450°C to 550°C, the time of the second calcination is 0.5h to 1.5h, and the atmosphere of the second calcination is a nitrogen atmosphere; the heating rate of the third calcination is 45°C / min to The temperature of the third calcination is 750°C to 850°C, the time of the third calcination is 0.5h to 1.5h, the atmosphere of the third calcination is a protective gas atmosphere, and the protection period includes at least one of helium, neon and argon; the heating rate of the fourth calcination is 55°C / min to 65°C / min, the temperature of the fourth calcination is 1200°C to 1400°C, the time of the fourth calcination is 11h to 13h, the atmosphere of the fourth calcination is a protective gas atmosphere, and the protection period includes at least one of helium, neon and argon.

[0080] Specifically, in this embodiment, the blank is sent to a microwave drying line, heated to 102°C at a rate of 8°C / min and dried for 1.5 hours, and then sent to a kiln for roasting after cooling. The roasting temperature program is to heat the air atmosphere to 200°C at a heating rate of 40°C / min and keep warm for 1 hour, and then switch to the nitrogen atmosphere at the same temperature. Then heat it to 500°C at a heating rate of 20°C / min and keep warm for 1 hour, and then heat it to 800°C at a heating rate of 50°C / min and keep warm for 1 hour. At the same temperature, switch to a protective gas (one or more of helium, neon, and argon) atmosphere, then heat it to 1300°C at a heating rate of 60°C / min, and finally heat it to 1460°C at a heating rate of 20°C / min, and heat it for 12 hours to obtain a cordierite ceramic carrier.

[0081] The cordierite ceramic carrier can be applied to automotive TWC ceramic carriers (400 / 600 / 750 / 900 meshes are all applicable), and the subsequent size grinding and skin grafting operations can be carried out by conventional means, which will not be repeated here.

[0082] The linear expansion coefficient of the cordierite ceramic carrier prepared by this method is 0.17*10 -6 ~0.28*10 -6 ℃ -1 , heat shock resistance temperature greater than 800℃, softening temperature greater than 1480℃, cordierite phase ≥93%, which can meet the high requirements for carrier performance. The raw materials are easy to obtain, the appropriate formula is combined with the improved firing process, the firing success rate is above 95%, and it is suitable for industrial mass production. And the surface and inner wall roughness of the finished cordierite ceramic carrier is greater than 1.2μm, which is conducive to subsequent coating.

[0083] Based on a general inventive concept, an embodiment of the present application further provides a cordierite ceramic carrier, wherein the cordierite ceramic carrier includes a carrier prepared by the method provided above.

[0084] The cordierite ceramic carrier is prepared based on the above method. The specific steps of the method can refer to the above embodiment. Since the cordierite ceramic carrier adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be repeated here.

[0085] The applicant has found that after the car is started, it takes a long time for the three-way catalytic converter to reach the ignition temperature of the three-way catalyst. Generally, the first 10 minutes after the car is started is the stage where the automobile exhaust emission pollution is the most serious.

[0086] In some embodiments, the cordierite ceramic carrier includes a carrier body and a heating device, wherein the carrier body includes a carrier prepared by the method provided above, and the heating device is installed on the carrier body. The setting of the heating device solves the problem of high evaporative emissions during the vehicle startup phase, and achieves a catalytic effect of ignition upon startup.

[0087] Furthermore, the heating device includes an electric heating device or an electromagnetic heating device.

[0088] In order to achieve electric heating or electromagnetic heating, a metal mesh single-end sheath is introduced here without affecting the carrier function. Specifically, a 0.1-0.5mm diameter resistance wire (Cr 20 Ni 80 Cr 30 Ni 70 Or Cr 15 Ni 60The braided sleeve is a kind of braided sleeve (one of which is braided at one end and unbraided at the other end), and the braiding density can be adjusted according to the matching carrier type. It is used as a net bag to cover the carrier body. The air inlet direction of the carrier body is braided, and the tail end is unbraided. The fuel vehicle is provided with a power source by the battery, and the hybrid vehicle is provided with an energy source by the battery or power battery. When the car receives the start command, the braided sleeve (i.e., the heating device) will be quickly powered on for heating, and the ambient temperature of the carrier will be raised to above 600°C within 8s, reaching the ignition temperature of the catalyst, so as to solve the problem of high evaporative emissions during the vehicle startup phase. In addition, the intake end face of the braided sleeve can be subjected to surface anodizing and other treatments to cover the surface with a relatively rough layer of γ-alumina, that is, to form a mesh catalyst carrier, and then platinum-based precious metals are coated on it to form a front catalyst. This structure quickly reaches the ignition temperature by short-circuit heating. The emission peak of the post-treatment device with a heating device during the cold start phase can be reduced by about 80%.

[0089] The structure of electromagnetic heating is similar to it, and the material needs to be replaced with stainless iron or iron alloy with higher magnetic permeability (relative magnetic permeability μr ≥ 300 is required). The cylindrical surface of the cylindrical sleeve is made of stainless iron or iron alloy skin coil welding that meets the requirements (thickness 1-1.5mm), and the intake end face is woven and prepared with iron alloy wire with a diameter of 0.1-0.5mm and welded or crimped to the cylindrical surface. The woven mesh of the same end face is subjected to surface anodizing and other treatments to cover its surface with a relatively rough layer of γ-alumina to form a mesh catalyst carrier, and then platinum-based precious metals are coated on it to form a front-end catalyst. Then a copper coil winding needs to be arranged on its outside. This solution is more suitable for hybrid vehicles, and the carrier ambient temperature can be raised to above 600°C within 10s.

[0090] Furthermore, the carrier body includes a first section and a second section, the first section is close to the air inlet end of the carrier body, and the heating device is installed on the first section.

[0091] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0092] It should be noted that the raw materials used in each embodiment and comparative example meet the following conditions:

[0093]

[0094] Example

[0095] A cordierite ceramic carrier, the preparation process of which is as follows:

[0096] Talc, calcined kaolin, raw kaolin, alumina, nano-active oxide, spherical fused silica SiO2, and aloe powder are mixed as solid materials according to the formula proportions in the following table to obtain a dry material.

[0097]

[0098]

[0099] The binder methyl cellulose and corn starch hydrolyzate (1:6, DE value ≤ 18), the lubricant magnesium stearate and purified water are prepared into wet material in a ratio of 3:1:12.

[0100] Finally, the dry material and the wet material were mixed and stirred (1000r / min) in a ratio of 68:32. After stirring for 30 minutes, they were put into a kneading machine for kneading and slurrying for 10 minutes to obtain a mixture.

[0101] Then, the mixed material was extruded at 10 cm / min and a pressure of 10 MPa to obtain a thin-wall honeycomb structure to obtain a billet.

[0102] The blank was sent to the microwave drying line, heated to 102°C at a rate of 8°C / min and dried for 1.5 hours. After cooling, it was sent to the kiln for roasting. The roasting temperature program is to heat the air atmosphere to 200°C at a heating rate of 40°C / min, keep warm for 1 hour, and then switch to the nitrogen atmosphere at the same temperature. Then heat it to 500°C at a heating rate of 20°C / min and keep warm for 1 hour, and then heat it to 800°C at a heating rate of 50°C / min and keep warm for 1 hour. At the same temperature, switch to a protective gas (one or more of helium, neon, and argon) atmosphere, then heat it to 1300°C at a heating rate of 60°C / min, and finally heat it to 1460°C at a heating rate of 20°C / min, and heat it for 12 hours to obtain a cordierite ceramic carrier.

[0103] Comparative Example

[0104] A cordierite ceramic carrier, the preparation process of which is as follows:

[0105] The raw materials include talc, kaolin, alumina, silica and cordierite powder as main materials, and the solid materials are mixed according to the formula proportions in the following table to obtain dry materials.

[0106] Alumina (%) Kaolin(%) Silicon oxide (%) talc(%) Cordierite powder(%) Comparative Example 1 18.13 36.25 5.04 40.58 0 Comparative Example 2 24.92 23.83 10.84 40.41 0 Comparative Example 3 26.46 19.31 14.53 39.2 0.5

[0107] The median particle sizes of the raw materials in the main material are: talc 25μm≥D 50 ≥5μm, Alumina 7μm≥D 50 ≥0.1μm, silicon oxide 15μm≥D 50≥1μm, kaolin 10μm≥D 50 ≥0.1μm, cordierite powder 25μm≥D 50 ≥1μm.

[0108] Taking the main material as 100wt%, the auxiliary materials include: 0-5wt% dispersant, 0-10wt% extrusion aid, 0-10wt% adhesive + plasticizer, 0-20wt% pore former, 20-26wt% water. There is no nano-level active additive in the formula. The chemical composition of cordierite in the main material cordierite powder is MgO: 12.5-14.5wt%, Al2O3: 33-37wt%, SiO2: 48-52wt%, and its crystal phase composition is cordierite ≥95%.

[0109] The sintering process is to increase the temperature from room temperature to 220°C at a rate of 12°C / h, then to 600°C at a rate of 15°C / h, then to 950°C at a rate of 25°C / h and keep it for 5 hours. Finally, it is increased to 1430°C at a rate of 25°C / h, kept for 12 hours and then cooled with the furnace. There is no special gas protection atmosphere in the whole process.

[0110] The performance of the cordierite ceramic carrier (750 / 2) provided in each embodiment and comparative example was tested, and the results are shown in the following table:

[0111]

[0112] It can be seen from the above table that the cordierite ceramic carrier prepared by the method provided in the examples of the present application has better performance and firing qualification rate.

[0113] The 750 / 2 cordierite ceramic carrier prepared in Example 1 of the present application (coated with a three-way catalyst of the same formula) was used, and the other test conditions were the same except for the presence or absence of electric heating configuration. The heating device was powered by a battery to simulate the instantaneous emission peak during cold start, and the results are shown in the following table:

[0114] THC(mg / s) CO(mg / s) NOX(mg / s) NMHC(mg / s) No heating device 8.00 65.22 18.56 6.13 With heating device (electric heating) 2.25 14.18 3.45 1.58

[0115] It can be seen from the above table that after installing the heating device, the emission peak can be suppressed by about 80%.

[0116] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0117] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple.

[0118] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a cordierite ceramic carrier, It is characterized in that The method comprises: dry-mixing the raw materials to obtain a dry material, wherein the raw materials include, by mass fraction, 8 to 16 parts of raw kaolin, 0 to 25 parts of calcined kaolin, 39 to 41 parts of talc, 8 to 22 parts of alumina, and 4 to 15 parts of silicon dioxide; The auxiliary agent is mixed with the solvent to obtain a wet material; kneading the dry material and the wet material to obtain a mixed material; Extruding the mixed material to obtain a blank; The green body is dried and then calcined to obtain a cordierite ceramic carrier.

2. The method for preparing the cordierite ceramic carrier according to claim 1, It is characterized in that In the raw kaolin, Al 2 O 3 The mass content of SiO is ≥37.50%, 2 Mass content ≥ 48.75%; and / or The mass loss on ignition of the raw kaolin is ≤13.0%; and / or The raw kaolin is in the form of flakes; and / or The D 50 7 μm to 9 μm; and / or The D 100 ≤63μm; and / or The diameter-to-thickness ratio of the raw kaolin is ≥30; and / or In the raw kaolin, K 2 O and Na 2 O mass content <0.5%, Fe 2 O 3 The mass content of TiO is ≤0.3%, 2 The mass content is ≤2.0%.

3. The method for preparing the cordierite ceramic carrier according to claim 1, It is characterized in that In the calcined kaolin, Al 2 O 3 The mass content of SiO is ≥43%, 2 The mass content of ≥52%; and / or The calcined kaolin is in the form of flakes; and / or The D 50 2 μm to 7 μm; and / or The D 100 ≤63μm; and / or The diameter-to-thickness ratio of the calcined kaolin is ≥30; and / or In the calcined kaolin, K 2 O and Na 2 O mass content <0.5%, Fe 2 O 3 The mass content of TiO is ≤0.3%, 2 The mass content is ≤2.0%.

4. The method for preparing the cordierite ceramic carrier according to claim 1, It is characterized in that In the talc, Al 2 O 3 The mass content of MgO is ≥ 62.54% and the mass content of MgO is ≥ 29.79%; and / or The mass loss on ignition of the talc is ≤13.0%; and / or The talc is in the form of flakes; and / or The D of talc 50 13 μm to 14 μm; and / or The D of talc 100 ≤63μm; and / or The diameter-to-thickness ratio of the talc is ≥30; and / or In the talc, the mass content of CaO is ≤0.1%, K 2 O and Na 2 O mass content <0.5%, Fe 2 O 3 The mass content of TiO is ≤0.9%, 2 The mass content of TiO is ≤2.0%, 2 The mass content is ≤0.1%.

5. The method for preparing the cordierite ceramic carrier according to claim 1, It is characterized in that In the alumina, Al 2 O 3 The mass content of ≥99%; and / or The D of the aluminum oxide 50 5 μm to 7 μm; and / or The diameter-to-thickness ratio of the aluminum oxide is ≥1; and / or In the alumina, Fe 2 O 3 The mass content of TiO is ≤0.003%, 2 The mass content of ≤0.03%; and / or In the silicon dioxide, SiO 2 The mass content of ≥99%; and / or The silicon dioxide satisfies: D 10 7.2~9.2μm, D 50 10.8~12.5μm, D 90 16.9 to 22 μm; and / or The particle size distribution parameter K of the silicon dioxide is 90 -D 10 ) / D 50 ) is 0.6~1.

6. The method for preparing the cordierite ceramic carrier according to claim 1, It is characterized in that The raw materials also include ultrafine nanometer active oxides, and the components of the ultrafine nanometer active oxides include Al 2 O 3 and SiO 2 ; and / or In the ultrafine nano-scale active oxide, Al 2 O 3 and SiO 2 The mass ratio is (0.5-1.5):(0.5-1.5); and / or The particle size of the ultrafine nano-scale active oxide is 20nm to 500nm; and / or The mass fraction of the ultrafine nanometer active oxide in the raw material is 8 to 12 parts.

7. The method for preparing the cordierite ceramic carrier according to claim 1, It is characterized in that The raw materials further include functional additives, and the functional additives include nano-aloe vera powder and / or blue algae powder; and / or The mass fraction of the functional additive in the raw material is 0.1 to 0.5 parts; and / or The particle size of the functional additive is 20nm to 400nm.

8. The method for preparing the cordierite ceramic carrier according to claim 1, It is characterized in that The drying temperature rise rate is 6°C / min to 10°C / min, the drying temperature is 90°C to 110°C, and the drying time is 1h to 2h; and / or The calcination includes a first calcination, a second calcination, a third calcination and a fourth calcination; and / or The heating rate of the first calcination is 35°C / min to 45°C / min, the temperature of the first calcination is 150°C to 250°C, the time of the first calcination is 0.5h to 1.5h, and the atmosphere of the first calcination is air atmosphere; and / or The heating rate of the second calcination is 15°C / min to 25°C / min, the temperature of the second calcination is 450°C to 550°C, the time of the second calcination is 0.5h to 1.5h, and the atmosphere of the second calcination is a nitrogen atmosphere; and / or The heating rate of the third calcination is 45°C / min to 55°C / min, the temperature of the third calcination is 750°C to 850°C, the time of the third calcination is 0.5h to 1.5h, the atmosphere of the third calcination is a protective gas atmosphere, and the protective period includes at least one of helium, neon and argon; and / or The heating rate of the fourth calcination is 55°C / min to 65°C / min, the temperature of the fourth calcination is 1200°C to 1400°C, the time of the fourth calcination is 11h to 13h, the atmosphere of the fourth calcination is a protective gas atmosphere, and the protective period includes at least one of helium, neon and argon.

9. A cordierite ceramic carrier, It is characterized in that The cordierite ceramic carrier is a cordierite ceramic carrier prepared by the method according to any one of claims 1 to 8.

10. The cordierite ceramic carrier according to claim 9, It is characterized in that The cordierite ceramic carrier comprises a carrier body and a heating device, wherein the carrier body comprises a carrier made by the method according to any one of claims 1 to 8, and the heating device is installed on the carrier body; and / or The heating device comprises an electric heating device or an electromagnetic heating device; and / or The carrier body comprises a first section and a second section, the first section is close to the air inlet end of the carrier body, and the heating device is installed on the first section.

Citation Information

Patent Citations

  • Porous ceramics catalyst carrier possessing two-dimensional nanopores and preparation method thereof

    CN105060861A

  • Thin-wall large-aperture cordierite honeycomb ceramic carrier and preparation method thereof

    CN111393155A

  • Cordierite heat shock resistant thin-wall catalyst carrier and preparation method thereof

    CN113912411A

  • Mixture composition for producing cordierite ceramics

    RU2818395C1

Cited By

  • Whisker reinforced composite porous ceramic material as well as preparation method and application thereof

    CN122010542A